Development of an innovative economy in Poland based on the transfer of knowledge from universities to the economy - Derlukiewicz, Niki (Rozwój innowacyjnej gospodarki w Polsce w oparciu o transfer wiedzy z uczelni wyższych do gospodarki, 2014)
What is extremely important in the modern economy is the ability to create and adapt new solutions, technologies, and to introduce new products and services. Innovation is currently a significant factor influencing the development of both businesses and regions or countries [Zalesko 2005, p. 683]. In the European Union and its Member States there is an increasing interest in innovations and their impact on the socio-economic development, as evidenced by the new Europe 2020 strategy of socioeconomic development of the European Union, in which innovations are a priority. It is increasingly emphasized that for the innovative economy to develop, the academic sector must cooperate with the economy in the process of both generating and implementing innovations. The article discusses the issue of cooperation between science and business in Poland for the development of innovation
Biblioteka Regionalisty, 2014, Nr 14, s. 7-14
Keywords: innovation; economy; knowledge; transfer